Pendidikan Islam di Spanyol Masa Modern - Muhammad Basri; Astri Syakira Sunya; Annisa Nasution (IKAMAS: Jurnal Informasi Keagamaan, Manajemen dan Strategi, 2024)
The purpose of this study is to find out how Islamic education is in modern Spain. This study uses the method of literature study. The results of this method show that Islamic education in modern Spain has experienced rapid development and Islamic education and Islamic culture, which began with the study of religion, science and literature, then increased with the study of sciences that have increased until now. Islamic education in modern Spain is very important and can make changes to education in the past before the arrival of Islamic education in Spain so that Islamic education has developed rapidly until now.